2009
DOI: 10.1007/s00535-009-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a monoclonal with a polyclonal antibody-based enzyme immunoassay stool test in diagnosing Helicobacter pylori infection after eradication therapy

Abstract: The new stool antigen test using monoclonal antibody is useful for the diagnosis of H. pylori eradication 4 weeks after the end of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
(18 reference statements)
0
22
0
4
Order By: Relevance
“…A meta-analysis of 22 studies including 2499 patients showed that laboratory SATs using monoclonal antibodies have a high accuracy both for initial and post-treatment diagnosis of H pylori 77. These data have been confirmed by more recent studies 78 79. In contrast, the rapid in-office tests have a limited accuracy 80 81…”
Section: Management Of H Pylori Infection (Workhop 2)mentioning
confidence: 78%
“…A meta-analysis of 22 studies including 2499 patients showed that laboratory SATs using monoclonal antibodies have a high accuracy both for initial and post-treatment diagnosis of H pylori 77. These data have been confirmed by more recent studies 78 79. In contrast, the rapid in-office tests have a limited accuracy 80 81…”
Section: Management Of H Pylori Infection (Workhop 2)mentioning
confidence: 78%
“…Additional studies have evaluated different stool tests: Deguchi et al. [47] compared a monoclonal stool antigen test (Testmate pylori antigen EIA ® (Wakamoto Pharmaceutical Co. Ltd., Tokyo, Japan)) with a polyclonal enzyme immunoassay (HpSA test ® ) post‐treatment in 150 patients (28 positive) using UBT as gold standard. Sensitivities were 92 and 87%, respectively, and specificity was 98% for both tests.…”
Section: Noninvasive Testsmentioning
confidence: 99%
“…Testmate pylori antigen (TPAg; Wakamoto Pharmaceutical Co., Ltd, Tokyo, Japan) utilizes monoclonal antibody to native H. pylori catalase [3,4] and is reported to be as accurate as UBT for the evaluation of the outcome of eradication therapy in Japanese patients [5,6]. However, the results of testing with TPAg cannot be obtained quickly because stool samples are usually transferred to central laboratories and subjected to enzyme immunoassay (EIA).…”
Section: Introductionmentioning
confidence: 99%